PENGENALAN AKSES KE PERBANKAN SYARIAH MELALUI PROGRAM MENJAGA KEBERSIHAN DAN KESEHATAN MASYARAKAT - Harly Setiawan; Tubagus Rifqy Thantawi; Azizah Mursyidah (SAHID DEVELOPMENT JOURNAL, 2021)
Abstract Covid 19 continues to grow in Indonesia. This condition makes all people in the country must be vigilant. Every individual has a responsibility to others, by not participating in spreading the Corona virus. The Indonesian government has now made efforts to break the chain of Covid 19. The appeals are to maintain physical distance (social distancing), work from home, study from home, to worship at home continue to be echoed. Various efforts to prevent the Covid 19 virus have been carried out by the community, especially the people of Kiara Payung Village, Ciasihan Village, Pamijahan District, Bogor Regency, starting from washing clean hands, using masks or face shields, avoiding crowded places or known as social distancing, not shaking hands temporarily, to maintain a distance of 1-2 meters from other people. The purpose of this activity is for the community to: (1) maintain health in order to stay healthy and avoid the Covid 19 virus (2) understand the importance of using masks when doing activities (3) making disinfectants and hand sanitizers (4) knowing how to wash hands properly, because Hand washing is one of the most effective ways to kill germs and viruses that enter the body. The conclusions are (1) The results of interviews with training participants about the use of masks, in general the trainees answered that sometimes they do not wear masks when leaving the house because of forgetting. (2) This activity is carried out by going directly to the field to help the village government so that residents are free from covid 19, during the activity of spraying disinfectants and distributing Handsanitizer we provide direction and knowledge about the dangers of covid 19. (3) Distribution of trash bins is carried out to implement a clean and healthy lifestyle, as well as making it easier for residents to dispose of garbage when they are in that place. Keywords: Covid-19 Virus, Health Protocol